The implementation of project-based learning to improve students' speaking skills: a systematic literature review - Iwan Dudy Gunawan (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2026)
This systematic literature review examines the implementation of Project-Based Learning (PBL) in improving students’ speaking skills in Indonesian EFL classrooms. The review analyzes 20 peer-reviewed journal articles published between 2020 and 2024, selected based on explicit inclusion criteria: empirical studies conducted in Indonesian EFL contexts, focusing on speaking skills, and employing PBL as the primary instructional approach. Data were synthesized using thematic content analysis to identify patterns of implementation, learning outcomes, and challenges. The findings indicate that PBL is commonly implemented through projects such as debates, storytelling, video-based tasks, and digital presentations. Compared to conventional teacher-centered methods, PBL demonstrates stronger effects on speaking fluency, confidence, vocabulary development, pronunciation, and communicative interaction. Different project types contribute to specific speaking outcomes, with storytelling enhancing pronunciation and intonation, while debates and presentations improve fluency and accuracy. However, several challenges persist, including limited instructional time, uneven group participation, insufficient teacher readiness, and technological constraints, which reflect broader structural and institutional issues. The study highlights the need for systematic scaffolding, teacher training, and curriculum alignment to support effective PBL implementation. Overall, the review confirms that PBL is a flexible and effective approach for enhancing speaking skills in Indonesian EFL contexts.